Intragastric pH of foals admitted to the intensive care unit. (29th September 2020) - Wise, Jessica C.; Raidal, Sharanne L.; Wilkes, Edwina J. A.; Hughes, Kristopher J.
Abstract: Background: Intragastric pH profiles of neonatal foals admitted to the intensive care unit (ICU) remain poorly characterized. Hypothesis/Objectives: To determine intragastric pH profiles and clinical parameters associated with intragastric pH in foals admitted to the ICU. Animals: Forty‐two neonatal foals admitted to the ICU and requiring placement of an indwelling nasogastric tube for nutritional management were included. Methods: Intragastric pH was measured for 24 hours from the time of admission. Mean pH, % time pH <4, and % time pH >4 were determined for each foal. History, clinical findings, and clinicopathological data recorded at the time of presentation were collected. Results: The mean pH of included foals was 5.5 ± 1.8. The median % time pH <4 was 6.3% (range: 0‐99). A history of placentitis was associated with greater mean pH (median 5.3 (range: 0.9‐7.8) versus median 7.2 (5.9‐11.3); P = .002) and less % time pH <4 (median 13 (0‐99.6) versus median 0.1 (0‐7.2); P = .01). Foals with diarrhea had a greater % time pH <4 (median 4.6% (0‐99) versus median 28.8% (1.4‐57.48); P = .02). Foals with a pH >4 for >50% recording time had a lower PaO2 (mean difference 25.0 mm Hg; 95% confidence interval [CI], 14.4‐35.6; P = .03) and higher PaCO2 (mean difference 14.9 mm Hg; 95% CI, 4.7‐25.2; P = .02). Surviving foals had a lower mean median hourly pH ( P = . 02). Conclusions and Clinical Importance: Intragastric pH profiles were unpredictable and mostly >4 for >80% of the recording time. This study does not support the indiscriminate administration of acid suppressive treatment.